Responsive regulation : transcending the deregulation debate - Ayres, Ian, 1959- (Oxford socio-legal studies., 1992)
This book transcends current debate on government regulation by lucidly outlining how regulations can be a fruitful combination of persuasion and sanctions. The regulation of business by the United States government is often ineffective despite being more adversarial in tone than in other nations. The authors draw on both empirical studies of regulation from around the world and modern game theory to illustrate innovative solutions to this problem. Their ideas include an argument for the empowerment of private and public interest groups in the regulatory process and a provocative discussion of.